Ectopic Lingual Thyroid - Khaled Khamassi; Habib Jaafoura; Fahmi Masmoudi; Rim Lahiani; Lobna Bougacha; Mamia Ben Salah (Case Reports in Pediatrics)
Ectopy of the thyroid gland is an abnormal embryological development. Its occurrence in children is rare. In this study, we report the case of a 12-year-old girl that presented with dysphagia and nocturnal dyspnea. Magnetic resonance imaging confirmed the presence of a lingual thyroid. Thyroid scintigraphy showed intense and elective uptake of radiotracer at the base of the tongue. Hormonal tests revealed hypothyroidism. Treatment consisted of opotherapy based on levothyroxine. Evolution has been favourable and the patient showed significant improvement with reduction of the dyspnea and the dysphagia and normalization of thyroid hormone tests.